Physical Educators Self-efficacy in the Implementation of the New Curriculum for the “New School- the School of the 21st century” - Gorozidis, Γεώργιος; Papaioannou, Αθανάσιος; Diggelidis, Νικόλαος (Inquiries in Physical Education and Sport, 2012)
Educational studies have been shown that teachers’ self-efficacy beliefs are essential determinants of the teaching outcomes and very important factors for the adoption of any reform effort. The scope of the present study was to examine Physical Education (PE) teachers’ self-efficacy in teaching the six basic standards (Std.) of the new national PE curriculum. As a part of the reform effort “New School- the school of the 21st century”, the new curriculum firstly introduced during the school year 2011-2012, to be piloted in 167 selected schools all over Greece. Participants were 92 PE teachers (48 male, 44 female/ 53 primary, 39 secondary school), from these pilot schools. Physical educators voluntarily responded in anonymous questionnaires measuring their self-efficacy beliefs to implement effectively the six main standards of the new curriculum. The six scales (one per standard) had acceptable levels of internal consistency (α > .70). Analyses showed that PE teachers held relatively high selfefficacy beliefs to implement most of the standards. However, one-way RM-ANOVA revealed that there were differences among the teachers’ self-efficacy on the six standards. Furthermore, MANOVA’s results exhibited that differences exist in self-efficacy between gender and school level. Women demonstrated higher levels of men, while primary school teachers had higher self-efficacy than secondary school teachers. Educators’ efficacy was lower in developing: students’ fitness level through their exercise self-regulation (Std. 3), a responsible sporting and social behavior (Std. 6), understanding and respect for diversity of people (Std. 5). The results imply that physical educators’ in-service training, need to be targeted to improve their selfefficacy, relative to specific curriculum standards, while during training their gender and school level need to be taken under consideration.